A Importância do Programa de Aquisição de Alimentos (PAA) nos territórios da cidadania dos Estados de Minas Gerais e da Bahia: Criação de novos mercados a partir da visão dos Agentes de Assistência Técnica e Extensão Rural (ATER) - Silva, Telma Coelho (2014)
This article aims to identify how the Foodstuff Acquisition Program has influenced market creation for family farmers in two Brazilian states - Minas Gerais e Bahia and also the limitations and benefits of the program from the point of view of the extension agents. A bibliographic research and a quantitative exploratory study were conducted, questionnaires were sent to extension agents who work for public rural extension agencies, municipalities, NGOs, cooperatives and producers' associations, during the year 2010-2011.